(untitled) (Journal of Student Affairs in Africa, 2023)
Abstract This study focused on the benefits for first-year university students who lived in the university residences at a South African University joining peer groups. A qualitative approach was adopted through a case study research design. Qualitative data were collected from first-year students in 2017 through three focus group interviews with females only, males only and mixed gender in two first-year residences at a selected South African university. The qualitative data were analysed using thematic analysis. The findings reveal the benefits for first-year students joining peer groups in the residences at the South African university, which include gaining a sense of belonging, receiving academic support, developing student leadership roles, and involving co-curricular activities. The study supports the need for implementing enchanted first-year student programs to assist first-year students in transitioning to higher education and decrease dropout rates.